2019
DOI: 10.1021/acs.macromol.9b01746
|View full text |Cite
|
Sign up to set email alerts
|

The “Superlubricity State” of Carbonaceous Fillers on Polyethylene-Based Composites in a Molten State

Abstract: It is very well known that the incorporation of fillers into polymers increases their viscosity in a molten state; however, results contrary to this have been reported when graphite (Gr), graphite oxide (GrO), and graphene oxide (GO) among other carbonaceous fillers are used. Many authors have justified the reduction in polymer viscosity due to the slipping interlayers of the Gr, GrO, and GO fillers. The slipping interlayer cannot explain the reduction in polymer viscosity since the shear stresses produced or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…From the viscosity curves it is possible to notice that all the studied compositions show (a) shear‐thinning behavior; (b) mGO behaves as a lubricant agent, easing the polymer flow through the capillary and reducing its shear viscosity relatively to pure PET; and (c) the amount of mGO is not high enough to induce different viscosity levels in the composites. This trend of decreasing viscosity was already reported by some works in the literature [ 28,34,37,39,53 ] and it is industrially interesting, because this effect may act as a “processing aid” during the composites compounding and molding, allowing the use of less severe parameters, such as lower temperature, torque and pressure. In order to confirm that the reason for these results are due to lubrication effects, viscometric analyses were carried out and the relative viscosities ( η r ) were obtained for the processed neat PET and all nanocomposites, as presented in Table 3.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…From the viscosity curves it is possible to notice that all the studied compositions show (a) shear‐thinning behavior; (b) mGO behaves as a lubricant agent, easing the polymer flow through the capillary and reducing its shear viscosity relatively to pure PET; and (c) the amount of mGO is not high enough to induce different viscosity levels in the composites. This trend of decreasing viscosity was already reported by some works in the literature [ 28,34,37,39,53 ] and it is industrially interesting, because this effect may act as a “processing aid” during the composites compounding and molding, allowing the use of less severe parameters, such as lower temperature, torque and pressure. In order to confirm that the reason for these results are due to lubrication effects, viscometric analyses were carried out and the relative viscosities ( η r ) were obtained for the processed neat PET and all nanocomposites, as presented in Table 3.…”
Section: Resultssupporting
confidence: 76%
“…These phenomena allow the filler to enter its "superlubricity state," that is, internal friction in the material flow is reduced, consequently, reducing its viscosity. On the other hand, when less shear stress is generated, it might not be enough to produce the effect reported by Ferreira et al [34] In this case, instead of easing the flow, the filler/filler and filler/polymer interactions will restrict the molecules mobility, which in turn increases the material's viscosity. Figure 8 exhibits the shear stresses present during the capillary and steady shear tests for neat PET.…”
Section: Steady Shear and Dynamic Oscillatory Testsmentioning
confidence: 93%
See 2 more Smart Citations
“…It can be observed that the d-spacing increase from 0.312 nm (Gr) to 0.895 nm (GrO 2 h) and 0.907 nm (GrO 96 h) due to the presence of oxygen functional groups, such as −OH and −COOH, obtained from the oxidation process [33]. The higher d-spacing obtained for the GrO 96 h is due to the higher oxidation time, which led to an increase in functional groups developed in the material structure [34]. As shown in Figure 3, the Raman spectrum can provide several bands, but the most important ones for carrying out the study and characterization of the load are the D, G, and 2D bands.…”
Section: Structural Characterization Of Graphene Oxidementioning
confidence: 96%